Tindak Tutur “Perlokusi” dalam Pembangunan Keluarga Harmonis: Pendekatan “Tertip” dalam Budaya Gayo - Joni, Joni; Syakur , Muh.; Rokhmat, Rokhmat; Atus Solikhah , Badik (El-Qenon: Journal of Islamic Law, 2024)
Speech acts are the acts of social activities and its aimed at interaction and communication in building of family harmony. This research to reveals how the speech acts can build harmony within the family. Through of this research, researcher able to reveal the patterns and standards of harmonious family life. This research was studied by qualitative methods with a pragmatic approach, it is through a “tertip” approach in Gayo cultures and the form of perlocutionary speech acts. The data extracted in this research is field data from 4 (four) families, they are transcribed verbal data, which in originates from daily speech acts of the parents with children and the children with parents. Speech acts in Gayo culture’s families, especially when the parents advise their children, give instructions to their wives and children, and express their gratitude to their wives. The results and findings in the research after analysis are that in Gayo culture there are orderly speech acts. Absolutely, the speech acts in this context are namely, the "Tengkah Bengkuwang Gewat" the speech act mode, namely speech acts that are indirect and is not literal, it is the speech acts using similes and similes (metaphors). The speech act patterns found in Gayo Community families, when they want to advise and teach their children and then to their wives, use perlocutionary speech acts, then focus in substance are commanding, and expositive. A harmonious, effective family uses the “tertip” speech act mode with the “bengkuwang gewat” behavior mode and understanding the felicities condition